2004
DOI: 10.1021/ja049245s
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of β-Amino Ester Enolates as Hexamers via 6Li NMR Spectroscopy

Abstract: As part of a program to prepare new antithrombotic agents, we discovered that unprotected -amino esters can be exclusively C-alkylated. We sought to optimize this process by studying the structures and reactivities of -amino ester enolates. 1 Determining the aggregation state of an enolate, however, is especially difficult due to the high symmetry of the possible aggregatessmonomers, dimers, tetramers, and hexamerssand the spectroscopically opaque Li-O linkage. 2 Herein we describe a spectroscopic method used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…An ensemble of homo- and heteroaggregated phenolates (eq 1) was monitored as a function of the mole fractions of phenolate subunits (denoted generically as A and B ) using 6 Li NMR spectroscopy 6,7. The number of aggregates and their symmetries reflect the aggregation state, n (Table 2; Chart 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An ensemble of homo- and heteroaggregated phenolates (eq 1) was monitored as a function of the mole fractions of phenolate subunits (denoted generically as A and B ) using 6 Li NMR spectroscopy 6,7. The number of aggregates and their symmetries reflect the aggregation state, n (Table 2; Chart 2).…”
Section: Resultsmentioning
confidence: 99%
“…The parametric fits show that all are nearly statistical distributions; non-statistical ensembles usually attest to deep-seated structural anomalies (vide infra). The math underlying the parametric fits has been discussed previously 6,7…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been shown that the C-alkylation of b-amino esters proceeds via hexameric enolates, which exist as such both in the solid state and in THF solution. 23 Based on the above observations, the existence of a C-lithiated ester enolate has been ruled out. Therefore, it is likely that O-versus C-silylation depends on the equilibrium between the two OLi structures, monomeric 'A' and aggregated 'B', as depicted in Scheme 1.…”
mentioning
confidence: 99%